Annual bulletin of statistics on cocoa, coffee & tea: 1981/82 Season - Nigerian Cocoa Board Statistical. Statistics Section; Nigerian Cocoa Board (Ibadan : Statistics Section, Nigerian Cocoa Board, 1984)
This is the statistical bulletin of the Nigerian Cocoa Board for the season 1981/82..
aia 07/02/2019, rpm 20/02/2019
Loans
Keywords: Cocoa trade; Coffee industry; Tea trade; Nigeria